Bioquímica sérica e eritrograma em ovinos da raça Morada Nova: influência da idade, do sexo e do escore corporal - Carlos, Maria Marília Leite (2010)
The present work aimed to determine the serum biochemical panel and erythocytogram from sheep of Morada Nova breed, and to verify the variation of these parameters promoted by gender, age and body condition score. The study was conducted in nine herds, two from Ceará state, five from Rio Grande do Norte state and two from Paraíba state, Brazil. It was used 249 clinically health sheep of Morada Nova breed; the gender, age and body condition score were recorded from each animal. It was collected blood samples for determination of the serum levels of glucose, cholesterol, triglycerides, urea, creatinine, total proteins, albumin, globulins and thyroxine (T4), the serum activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), the number of erythrocytes, and the packed cell volume (PCV). From the obtained results, it was observed that the number of erythrocytes and PCV from Morada Nova sheep were equivalent to the average of those presented by the remaining sheep. Furthermore, the evaluated serum biochemical panel from Morada Nova sheep did not present variation from the reference interval established for the species, except for lower levels of globulins and higher albumin/globulins ratio. It was also verified that the serum biochemical panel was affected by gender, age, and body score condition.